Analisis Kemampuan Kerja Dan Pembagian Kerja Terhadap Efektifitas Kerja Pegawai Kantor Kementerian Agama Kabupaten Labuhanbatu Selatan - Ade Trya Amanda; Nur'ainun Gulo (Jurnal Manajemen Akuntansi (JUMSI), 2025)
The purpose of this study was to determine the effect of work ability and job division on the work effectiveness of employees at the Office of the Ministry of Religious Affairs of South Labuhanbatu Regency. The sample in this study consisted of 46 respondents. Data were collected through interviews and questionnaires. The results of the F-test showed that Fcount (0.703) < Ftable (2.82) with a significance level of 0.501 > 0.05. This indicates that the variables of work ability (X1) and job division (X2) simultaneously do not have a significant effect on work effectiveness (Y). Therefore, the hypothesis stating that work ability and job division simultaneously have no positive and significant effect on the work effectiveness of employees at the Office of the Ministry of Religious Affairs of South Labuhanbatu Regency is accepted. Furthermore, the results of the t-test for the work ability variable (X1) showed that tcount (-1.080) < ttable (1.681) with a significance level of 0.286 > 0.05 (5%). Meanwhile, the job division variable (X2) showed that tcount (0.628) < ttable (1.681) with a significance level of 0.534 > 0.05. These results indicate that partially, work ability (X1) does not have a significant effect on work effectiveness (Y), and job division (X2) also does not have a significant effect on work effectiveness (Y). Thus, it can be concluded that work ability and job division, both simultaneously and partially, do not have a positive and significant effect on the work effectiveness of employees at the Office of the Ministry of Religious Affairs of South Labuhanbatu Regency.